Peningkatan Digitalisasi Branding dan Akses Permodalan untuk Mendorong UMKM Naik Kelas melalui Pendampingan Terintegrasi di Kabupaten Pekalongan (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in national economic development. However, many still face challenges in digital branding and access to formal financing. This community engagement program aimed to enhance the capacity of MSMEs through digital branding training, social media optimization, marketplace strengthening, financial literacy improvement, and assistance in accessing business financing. The program adopted a Participatory Action Research (PAR) approach, consisting of needs assessment, training, implementation assistance, monitoring, and evaluation. It was conducted over a four-month period involving culinary-sector MSMEs in Pekalongan Regency, Indonesia. The results demonstrated significant improvements in participants' ability to develop brand identities, manage business social media accounts, prepare simple financial statements, and understand the procedures for applying for the People's Business Credit (Kredit Usaha Rakyat/KUR) program. The program also produced several tangible outputs, including active social media business accounts, digital promotional content, simplified financial reports, and financing application documents. The findings indicate that an integrated approach combining digital branding and financial literacy effectively enhances MSMEs' readiness to become more professional, competitive, and financially sustainable.